The Metarhizium anisopliae Metsch. (Moniliales: Moniliaceae) and Aglaia odorata Lour. (Sapindales: Maliaceae) leaf extract: a potent biopesticide cocktail for cabbage leaf caterpillar management - Prastowo , Sigit; Wardhani, Widi Kusuma; Pradana, Ankardiansyah Pandu; Wafa, Ali; Addy, Hardian Susilo; Hadi, Zul Fauzi Nugroho (Universitas Lampung, 2024)
Plutella xylostella Linnaeus (Lepidoptera: Plutellidaae) is an important pest on Brassicaceae plants, especially cabbage. The combination of entomopathogenic fungi and botanical pesticides has been widely developed to increase effectiveness effectiveness against P. xylostella . This research aimed to determine the potential of Metarhizium anisopliae and Aglaia odorata Leaf Extract (Ao-LE) as a combined control strategy for P. xylostella. The parameters observed in this research were colony growth, viability of conidia of M. anisopliae, antifeedant activity, mortality, and lethal time 50 (LT50) of P. xylostella . The findings revealed that Ao-LE addition maintained colony growth comparable to that of the control treatment, while significantly enhancing the conidial viability of M. anisopliae. Notably, 0.80% and 1.00% Ao-LE in the M. anisopliae suspension resulted in maximum antifeeding activity. Moreover, incorporating 0.20-1.00% Ao-LE demonstrably improved P. xylostella mortality compared with M. anisopliae alone. The combination of M. anisopliae 107 conidia/mL and 1.00% Ao-LE exhibited the lowest LT50 value of 2.16 days, highlighting the synergistic effect of the combined treatment. In conclusion, this study provides compelling evidence for the compatibility and synergistic potential of M. anisopliae and Ao-LE, presenting a promising strategy for the sustainable management of P. xylostella infestations.